2018
DOI: 10.1016/j.ymthe.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Lung-Cancer-Derived Extracellular Vesicle MicroRNA-103a Increases the Oncogenic Effects of Macrophages by Targeting PTEN

Abstract: Hypoxia, the most commonly observed characteristic in cancers, is implicated in the establishment of an immunosuppressive niche. Recent studies have indicated that extracellular vesicle (EV)-mediated cancer-stroma interactions are considered to play a critical role in the regulation of various cellular biological functions, with phenotypic consequences in recipient cells. However, the mechanisms underlying the relationship between EVs and hypoxia during cancer progression remain largely unknown. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
146
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(152 citation statements)
references
References 40 publications
6
146
0
Order By: Relevance
“…Previous studies have confirmed that ADAM10 was a target of miR‐103a‐3p, and silencing of ADAM10 abated the inflammation of murine abdominal aorta . Moreover, miR‐103a‐3p negatively regulates PTEN expression, leads to the increased expression of immunosuppressive factors in lung cancer cells . Jung's team proved that mutations of TBL1XR1 increased pro‐inflammatory cytokines, leading to severe multi‐organ inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have confirmed that ADAM10 was a target of miR‐103a‐3p, and silencing of ADAM10 abated the inflammation of murine abdominal aorta . Moreover, miR‐103a‐3p negatively regulates PTEN expression, leads to the increased expression of immunosuppressive factors in lung cancer cells . Jung's team proved that mutations of TBL1XR1 increased pro‐inflammatory cytokines, leading to severe multi‐organ inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…34 Moreover, miR-103a-3p negatively regulates PTEN expression, leads to the increased expression of immunosuppressive factors in lung cancer cells. 35 Jung's team proved that mutations of TBL1XR1 increased pro-inflammatory cytokines, leading to severe multi-organ inflammation. In our work, we found that exosomal miR-103a-3p binds directly to a specific region of TBL1XR1, inhibiting LPS-induced immune response, which is consistent with Jung et al's finding.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that the level of PTEN in NSCLC cell lines was markedly decreased, and that the overexpression of hsa_circ_0033155 significantly enhanced the level of PTEN, revealing the regulatory role of hsa_circ_0033155 on PTEN expression. Emerging studies have demonstrated that circRNA functions as miRNA sponges, removing the inhibitory effect of miRNA on its target genes, and further regulating the expression of target genes, including PTEN (26,27). The miRNA that is regulated by hsa_circ_0033155, subsequently regulating the level of PTEN remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al investigated the relationship between EVs and hypoxia upon lung cancer progression [137]. They found that EV-encapsulated miR-103a levels were higher in patients with lung cancer and closely associated with macrophage M2 polarization.…”
Section: Lung Cancermentioning
confidence: 99%